Strategi Membangun Keluarga Sakinah: Refleksi Pemikiran Syaikh Muhammad Bin Shalih Al Utsaimin di Zaman Modern - Astri Cahya Anita; Ahyat Habibi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study aims to examine the concept and strategies for building a sakinah (harmonious and tranquil) family based on the thoughts of Shaykh Muhammad bin Shalih Al-Utsaimin and their relevance in the modern era. This research employs a qualitative method using a library research approach by analyzing Al-Utsaimin’s works, such as Majmu’ Fatawa wa Rasail and Syarh Riyadhus Shalihin, along with classical and contemporary literature related to the Islamic concept of family. The findings reveal that Al-Utsaimin’s strategies for establishing a sakinah family include a strong foundation of tawheed (Islamic monotheism) and sincere marriage intentions, a just and balanced division of roles between husband and wife, piety as the core of family life, ethical communication, and child education based on Islamic values. These strategies are highly relevant in addressing modern challenges such as rising divorce rates, the erosion of family roles, and negative media influences. Al-Utsaimin’s perspective provides practical and applicable guidance to strengthen Muslim family institutions that are harmonious and resilient amidst contemporary social dynamics.